Improving implementation of needle and syringe programmes to expand, scale up, and sustain evidence-based prevention interventions for HIV and hepatitis C in prisons - Kronfli, Nadine; Bromberg, Daniel J.; Wolff, Hans; Montanari, Linda; Vasyliev, Serheii; Altice, Frederick L (The lancet. Public health, 2024)
The 1990 resolution by the UN General Assembly committed member states to provide health-care equity for people in prison, who are included in the global goals to control HIV and eliminate hepatitis C virus (HCV) by 2030. WHO has set ambitious HCV elimination targets by including people who inject drugs (PWID), yet has not prioritised PWID who are incarcerated, a substantial population who have or are at risk for HCV infection. Human rights principles of health-care equity stipulate that “prisoners should enjoy the same standards of health care that are available in the community, without discrimination on the grounds of their legal status”. Globally, only nine countries provide prison-based needle and syringe programmes (PNSPs), essential evidence-based interventions to holistically reduce the harms from drug use, of which only three countries extend reach to all prisons. Even where available, these services are accessed by few participants. PNSPs are recommended as an essential element of an effective HIV and HCV prevention strategy in prisons, and studies have shown that they are key to achieving HCV elimination in carceral settings. This Viewpoint, based primarily on unpublished data from key country-level stakeholders and expert opinion, highlights our perspective that implementation factors related to PNSP delivery in diverse settings likely contribute to low adoption and use of these services by PWID in prisons compared with in the community. However, successful expansion of these evidence-based interventions will depend on political commitment, national surveillance and monitoring programmes, and state-of-the-art implementation science methods, where inputs from multilevel stakeholders should guide improved implementation. Policy makers are urged to create and support opportunities to scale up PNSPs within countries where they exist and expand them to other countries where they are needed to solidify years of commitment towards the 2030 HCV elimination goals.